Relationship between susceptibility to normative influence and purchase intention towards global brands in Nigeria - Anthony, Omaze Afamefuna (Center for Promoting Ideas, 2016)
Due to recent globalization has led to increase with many foreign companies competing with each other making consumers purchase intention more important issues for marketers and difficult to understand. Recent study has shown that norms of groups’ they associated influence consumer purchase intention. The present study was conducted to determine the relationship between susceptibility to normative and purchase intention towards global brand among consumers living in Nigeria. A total of 318 respondents were involved in this study, and they were selected based on the three local government areas in Lagos state which represent the three senatorial districts in the state. A quantitative research which employ questionnaire for data collection, and respondents were recruited using simple random sampling among Nigeria consumers living in Lagos state. Correlation analysis was used to examine the relationship between susceptibility to normative influence and purchase intention towards global brands. Result of this study showed that susceptibility to normative influence has a positive significant relationship with purchase intention towards global brands. This means that consumers with better orientation are motivated to purchase global brand in order to display their status and success to social group they belong. Consumer with higher susceptibity to normative influence is been dominant when buying brands that motivates them effectively in nature, regardless of product that is attracting attention by being impressive. Thus, it is recommended that local companies and marketers need to provide those products that increase the self-esteem of the consumers. They also need to identify the type of products that the consumers used frequently that gives them respect and sense of belongings, at the same time, need to regulate the quality of product that can compete with the foreign products.